PENERAPAN MODEL PEMBELAJARAN MIND MAPPING UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA TEMA DAERAH TEMPAT TINGGALKU DI KELAS IV SD NEGERI 060914 KEC.MEDAN SUNGGAL TAHUN PEMBELAJARAN 2018/2019 - MANULLANG, MERLIDYAWATI; SILABAN, PATRI JANSON (Unversitas Katolik Santo Thomas, 2020)
This researcher aims to improve student learning outcomes by using the Mind Mapping learning model in My Residential Area Theme in class IV-B Public Elementary School 060914 Kec. Medan Sunggal Learning Year 2018/2019.Â This research is a classroom action research (CAR), the subjects in this study were students of class IV-B SD Negeri 060914 Kec. Medan Sunggal. The results of this study indicate an increase in student learning outcomes on the theme of the Area of My Residence Proud Subtema Against My Residence Area in class IV-B Public Elementary School 060914 Kec Medan Sunggal Learning Year 2018/2019. The results of the study in the first cycle of students who received complete grades as many as 16 students or 57% while students who did not complete 12 students or 43% with an average value of 68. In cycle II, namely students who get complete grades 26 students or 93% while students who do not complete as many as 2 students or 7% with an average value of 87,5 then an increase from the first cycle compared to the second cycle and has met the specified completeness . Furthermore, the teacher's activities in the observation cycle I obtained an average of 64% and in the second cycle increased to 90%. While the activities of students in the learning process cycle I obtained an average of 58 and the second cycle had experienced an increase of 82. The results of this study showed an increase in learning outcomes by using the Mind Mapping learning model on the theme of My Residence Area IV-B Public Elementary School 060914 Kec Medan Sunggal Learning Year 2018/2019